PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA KARYAWAN GENERASI Z DI PT DIGDAYA BERKAH INDONESIA - Anbrilla; Christantius Dwiatmadja; Ardiani Ika Sulistyawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to examine the effect of Leadership Style and Compensation on Job Satisfaction, with Motivation as an intervening variable, among Generation Z employees at PT. Digdaya Berkah Indonesia, Semarang Regency, Central Java. The research employed a quantitative approach, distributing closed-ended questionnaires to 57 Generation Z employees at the company. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The results indicate that Leadership Style does not have a significant effect on Job Satisfaction, while Compensation has a positive and significant effect on Job Satisfaction. Leadership Style has a positive and significant effect on Motivation, and Motivation in turn has a significant effect on Job Satisfaction. Moreover, there is a very strong relationship between Compensation and Motivation.